A Distributed T-Way Test Suite Generation Using “One-Parameter-at-a-Time” Approach - Kamal Z., Zamli; H. C. Soh, Zainal; Syahrul A. C., Abdullah (Soft Computing Research Group,UTM Malaysia (SCRG Publication), 2013)

(untitled)
This paper presents a new distributed test suite generation for t-way testing, called TS_OP, using Map and Reduce software framework based on tuple space technology environment. TS_OP takes a oneparameter-at-a-time strategy and is capable of supporting high interaction strength (i.e. t>5). Internally, TS_OP coordinates and distributes the test case generation workload amongst participating workstations. An encouraging result is obtained from experimentation on the optimality of test suite size generated and on the speedup gain in multiple machine environments. Benchmarking studies in term of size of generated test suite against existing parameter based strategies (i.e.IPOG, MIPOG, IPOG-D, IPOG-F and IPOG-F2) indicate that TS_OP gives competitive results.